2015
DOI: 10.1097/jsa.0000000000000091
|View full text |Cite
|
Sign up to set email alerts
|

Does Femoroacetabular Impingement Contribute to the Development of Hip Osteoarthritis? A Systematic Review

Abstract: Femoroacetabular impingement (FAI) has been linked to specific patterns of cartilage damage. The goal of this systematic review is to answer the following questions: (1) Does FAI contribute to the development and progression of hip osteoarthritis (OA)? (2) If FAI does contribute to the development and progression of hip OA, does CAM-type or pincer-type impingement play a greater role? A search of the electronic databases, MEDLINE and EMBASE, was performed to identify relevant studies performed between January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 46 publications
1
42
0
2
Order By: Relevance
“…A list of articles consisting of recent systematic reviews and original seminal research relevant to these topics was prepared; panel members suggested additional articles where important research had been omitted. The revised selection of publications was provided to all panel members along with the following final questions: What is FAI syndrome?3 15–17How should FAI syndrome be diagnosed?8 11 18–21What is the appropriate treatment of FAI syndrome?9 22–28What is the prognosis of FAI syndrome?13 29How should someone with an asymptomatic hip with cam or pincer morphology be managed?30 31Which outcome measures should be used to assess treatment for FAI syndrome?32–34What future research needs to be conducted?…”
Section: Methodsmentioning
confidence: 99%
“…A list of articles consisting of recent systematic reviews and original seminal research relevant to these topics was prepared; panel members suggested additional articles where important research had been omitted. The revised selection of publications was provided to all panel members along with the following final questions: What is FAI syndrome?3 15–17How should FAI syndrome be diagnosed?8 11 18–21What is the appropriate treatment of FAI syndrome?9 22–28What is the prognosis of FAI syndrome?13 29How should someone with an asymptomatic hip with cam or pincer morphology be managed?30 31Which outcome measures should be used to assess treatment for FAI syndrome?32–34What future research needs to be conducted?…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have demonstrated an association between the presence of FAI morphology and cartilage damage [38, 43, 44, 63, 64, 65, 66, 67, 68]. For example, a study in which 244 asymptomatic young males underwent MRI found that the 67 participants with cam lesions had increased occurrence of labral lesions, impingement pits, and labral deformities [64].…”
Section: Etiology and Risk Factors For Hip Oamentioning
confidence: 99%
“…Over the last 15 years there has been an exponential growth in the arena of hip preservation surgery (both open and arthroscopic) in young adults in an attempt to prevent degenerative changes and perhaps delay or abort the need for arthroplasty in these patients. The evidence to support this theory has been growing steadily with a recent systematic review looking at 35 studies published between 2003 and 2014 investigating the relationship between FAI and OA [13]. The authors’ looked at all the human studies with more than five patients published since 2000.…”
Section: Does Fai Contribute To the Development Of Hip Osteoarthritismentioning
confidence: 99%
“…This in itself shows that although the number of procedures and even numbers of studies are increasing, there is still a lack of high-quality evidence in order to support or refute the mechanical theory. In this systematic review, the majority of studies used radiological criteria alone to make the diagnosis of FAI [13]. The authors’ concluded that there was a correlation found between FAI and OA, and an alpha angle of >60° was a predisposing factor to the development of significant OA which may then require a THR.…”
Section: Does Fai Contribute To the Development Of Hip Osteoarthritismentioning
confidence: 99%
See 1 more Smart Citation